Resilience and Employee Well-being in Times of Political Demonstrations: A Literature Review - Budiman Abdulah; Dewa Putu Yohanes Agata L. Sandopart (Airlangga Journal of Innovation Management, 2025)
This study presents the results of an analysis of scientific trends and developments related to resilience and employee well-being during the period 2020–2025, encompassing 225 articles, 214 keywords, and 622 authors, with particular attention to issues concerning social dynamics and political demonstrations. This research aims to (1) map the development of publications and citation trends related to resilience and employee well-being; (2) identify the most influential authors, countries, and research collaborations; (3) evaluate the main themes and shifts in research focus throughout the study period; and (4) assess the extent to which resilience and employee well-being are linked to the context of political demonstrations in the global literature. This study employs a bibliometric approach, reviewing publication counts, citation trends, geographical distribution of research, and dominant themes. The results indicate an increase in the number of publications from 25 articles in 2020 to 48 articles in 2024, followed by a slight decrease in 2025 (45 articles). Citation trends declined from an average of 33.6 in 2020 to 1.36 in 2025, reflecting a time lag in the accumulation of scientific impact. The most prominent topics include employee well-being and well-being, followed by burnout, job satisfaction, and employee engagement. These findings illustrate that employee resilience and well-being have become a matter of international concern and that research specifically examining the relationship between the two and political demonstrations remains limited. In practical terms, this study recommends the need for organizational strategies and public policies that improve mental health support, work flexibility, and employee well-being holistically.